FLOWERING PHENOLOGY OF APRICOT CULTIVARS IN THE REGION OF BELGRADE - Milatović, Dragan P; Zec, Gordan; Đurović, Dejan; Ruml, Mirjana (Journal of Agricultural Sciences (Belgrade), 2020)
The phenology of flowering was studied in 50 apricot cultivars in the region of Belgrade over a period of eight years (2009–2016). Within the flowering phenophase, three sub-phases have been registered: the beginning of flowering, full flowering and the end of flowering. In addition, the duration and intensity of flowering were examined. The average date of the start of flowering for all cultivars was March 22, of full flowering March 25, and of the end of flowering April 1. The average duration of flowering was 9.7 days, with a range among cultivars between 7.5 days (‛Gerganaʼ) and 12 days (‛Ninfaʼ and ‛Radkaʼ). The lowest average score (3.0) for flowering intensity was obtained in ‛Hungarian Bestʼ cultivar, and the highest score (4.6) in ‛Harcotʼ and ‛Leskoraʼ cultivars. In years with higher temperatures during the flowering, a smaller range in flowering time among cultivars was recorded, as well as shorter duration of flowering. Based on the start of flowering, the tested cultivars were divided into three groups: early-flowering (14 cultivars), medium-flowering (21 cultivars) and late-flowering (15 cultivars). Meteorological factors (air temperature) had a greater influence on the course and duration of flowering phenophase than the genetic traits of the cultivars.